TINGKAT PENGETAHUAN DAN SIKAP MAHASISWA FARMASI DAN NON FARMASI TERHADAP PENGGUNAAN TABIR SURYA - Hesti Hesti; Ida Ida; Tajuddin Abdullah (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2022)
Indonesia is a tropical country that is blessed with an abundance of sunlight which causes the importance of skin protection. One of them is the use of sunscreen. The correct application of sunscreen greatly affects its effectiveness in providing protection. Knowledge is one of the factors that support the use of sunscreen. One of the fields studied by pharmacy students is cosmetics. This study was conducted to compare the level of knowledge and attitudes of pharmacy and non-pharmaceutical students towards the use of sunscreen. This study is a descriptive study using a cross sectional design. Sampling in this study using the table Isaac and Michael. The data collection technique used a questionnaire that was filled out online consisting of 14 questions about knowledge and 21 questions about attitudes. The results showed that pharmacy and non-pharmaceutical students had a bad level of knowledge with scores of 17 and 16 respectively. Meanwhile, the attitude level of the two majors was good with scores of 39 and 38, respectively. After the Mann Whitney test was carried out, there was a significant difference at the level of knowledge between pharmacy and non-pharmaceutical students (P=0.000). However, at the attitude level, there was no significant difference (P=0.578). These results indicate that pharmacy students have a better level of knowledge than non-pharmacy students, although they are still in the same category, namely bad. So education related to sunscreen needs to be done to improve this condition.